Friends. Season 4 [videorecording (DVD)] - Aniston, Jennifer; Cox, Courteney, 1964-; Kudrow, Lisa; LeBlanc, Matt; Perry, Matthew, 1969-2023; Schwimmer, David, 1966- (Warner Bros. Entertainment Inc., 2019)
"Monica and Rachel are forced to switch apartments with Joey and Chandler, Phoebe's uterus is put to the test, and Ross pops the question to someone who's not Rachel."--Container.